In Silico, Molecular Docking and In Vitro Antimicrobial Activity of the Major Rapeseed Seed Storage Proteins - Rahman, Mahmudur; Browne, Jessica J.; Van Crugten, Jacoba; Hasan, Md. Fahim; Liu, Lei; Barkla, Bronwyn J. (Frontiers in Pharmacology, 2020)
Background In addition to their use as an edible oil and condiment crop, mustard and rapeseed (Brassica napus L., B. juncea (L.) Czern., B. nigra (L.) W.D.J.Koch, B. rapa L. and Sinapis alba L.) have been commonly used in traditional medicine for relieving pain, coughs and treating infections. The seeds contain high amounts of oil, while the remaining by-product meal after oil extraction, about 40% of seed dry weight, has a low value despite its high protein-content (~85%). The seed storage proteins (SSP) 2S albumin-type napin and 12S globulin-type cruciferin are the two predominant proteins in the seeds and show potential for value adding to the waste stream; however, information on their biological activities is scarce. In this study, purified napin and cruciferin were tested using in silico, molecular docking, and in vitro approaches for their bioactivity as antimicrobial peptides. Materials and Methods The 3D-structure of 2S albumin and 12S globulin storage proteins from B. napus were investigated to predict antimicrobial activity employing an antimicrobial peptide database survey. To gain deeper insights into the potential antimicrobial activity of these SSP, in silico molecular docking was performed. The purified B. napus cruciferin and napin were then tested against both Gram-positive and Gram-negative bacteria for in vitro antimicrobial activity by disc diffusion and microdilution antimicrobial susceptibility testing. Results In silico analysis demonstrated both SSP share similar 3D-structure with other well studied antimicrobial proteins. Molecular docking revealed that the proteins exhibited high binding energy to bacterial enzymes. Cruciferin and napin proteins appeared as a double triplet and a single doublet, respectively, following SDS-PAGE. SDS-PAGE and Western blotting also confirmed the purity of the protein samples used for assessment of antimicrobial activity. Antimicrobial susceptibility testing provided strong evidence for antimicrobial activity for the purified napin protein; however, cruciferin showed no antimicrobial activity, even at the highest dose applied. Discussion In silico and molecular docking results presented evidence for the potential antimicrobial activity of rapeseed cruciferin and napin SSP. However, only the in vitro antimicrobial activity of napin was confirmed. These findings warrant further investigation of this SSP protein as a potential new agent against infectious disease.